The Correlation of Reduced Fractional Anisotropy in the Cingulum With Suicide Risk in Bipolar Disorder - Tian, Fangfang; Wang, Xiuli; Long, Xipeng; Roberts, Neil; Feng, Can; Yue, Suping; Jia, Zhiyun (Frontiers in Psychiatry, 2021)
Objective: This study aims to investigate the significant alterations in brain white matter integrity in individuals with Bipolar Disorder (BD) who had attempted suicide by applying Tract-based spatial statistics (TBSS) approach with tensor-based spatial normalization. Methods: TBSS approach with novel tensor-based registration was used to compare the white matter Fractional Anisotropy (FA) between 51 individuals with BD, of whom 19 had attempted suicide, and 43 healthy controls (HC). The suicide attempt was assessed with the Columbia–Suicide Severity Rating Scale (C-SSRS). In addition, we also investigated the correlations of FA values with clinical measures in BD, including illness duration, the severity of depression and anxiety measured by the Hamilton Depression Rating Scale (HAMD) and Hamilton Anxiety Rating Scale (HAMA), respectively. Results: Significant reduction of FA value in the hippocampal cingulum was observed in BD individuals who had attempted suicide compared with those who had not. For the genu/body of the corpus callosum, inferior fronto-occipital fasciculus, uncinate fasciculus and anterior thalamic radiation, the reductions in FA values were significantly greater in both BD subgroups who attempted suicide and who did not, compared to HC. The correlation analysis showed that the illness duration of attempters was correlated to the FA value of genu of corpus callosum, while the HAMD and HAMA scores of non-attempters were relevant to the FA of superior longitudinal fasciculus. Conclusion: The observation that white matter integrity was altered in the hippocampal cingulum in BD individuals who attempted suicide suggested that this brain area may be the neurobiological basis of suicide attempts. Our findings also support the involvement of WM microstructure of frontal–subcortical circuits in the neurobiological mechanism of BD. In addition, the illness duration of patients with attempted suicide may have an effect on the altered integrity of corpus callosum.